Internet blackouts in Africa - Floribert Patrick C. Endong (Digital Policy Studies)
Internet blackouts in Africa have largely been examined through the prisms of human rights and economic development. This has resulted in highly negative assessments; Internet shutdowns have widely been branded as violations of the rights of African citizens, and the bane of economic development. However, while unarguably extreme, Internet blackouts are not necessarily unjustified or unwarranted. Even influential bodies such as the International Telecommunications Union (ITU) recognise the need to shut down the Internet under certain circumstances. Governments often justify Internet shutdowns by citing principles or values that are valid in principle. These include protecting their sovereignty, combating ‘rascality’ among telecom operators, and maintaining peace and security. Given this, it is important to examine the extent to which Internet shutdowns in Africa have been justified, or whether they have been used to advance authoritarian rule. To this end, this study uses documentary analysis and critical observations to explore the morality of Internet blackouts in sub-Saharan Africa, and specifically whether or not the recent shutdowns in Cameroon and Nigeria have been justified.